Analisa Perjanjian Tertutup dalam Pasal 15 Ayat (3) UU No. 5 Tahun 1999 dalam Perspektif Normatif dan Implementasinya - Kamser Lumbanradja; Dhaniswara K. Harjono; Hulman Panjaitan (Bulletin of Community Engagement, 2024)
To create a conducive business climate and to avoid unhealthy business competition, which can harm fellow business actors, including guaranteeing the quality of goods and services produced for the benefit of society as consumers, it is necessary to have legal institutions that regulate orderly business competition, known as the Business Competition Law. In Indonesia, the normative provisions of business competition law are regulated in Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. In this connection, Law No. 5 of 1999 has regulated and established a number of rules aimed at creating a conducive business climate and healthy business competition, including through the regulation of prohibited closed agreements as regulated in Article 15 of Law No. 5 of 1999. Regulations come in various forms and types, all of which aim to create a conducive business climate and avoid unhealthy business competition, which can harm all parties.